Art and Architecture in Canada : a Bibliography and Guide to the Literature. - Lerner, Loren R.; Williamson, Mary F. (University of Toronto Press, 1991)
Identifies and summarizes thousands of books, article, exhibition catalogues, government publications, and theses published in many countries and in several languages from the early nineteenth century to 1981.